2018
DOI: 10.1016/j.idairyj.2018.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Some aspects of the ethanol stability of red deer milk (Cervus elaphus hispanicus): A comparison with other dairy species

Abstract: The ethanol stability, a freshness and heat stability indicator, of Iberian red deer milk was determined. Additionally, the interspecific differences in composition, physical, hygienic and technological parameters, in bulk tank milk obtained from red deer, sheep, goats and cows were compared. Red deer milk ethanol stability was similar to that of sheep milk; bovine milk was the most stable and goat milk the least. Ethanol stability was influenced by pH; within the range studied, increased pH increased stabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 57 publications
3
14
1
Order By: Relevance
“…By contrast, milk electrical conductivity (EC) significantly increased, starting from the tenth week during lactation, from 2.31 to 3.56 mS/cm ( Table 4 ). These values were higher than those described for buffalo [ 18 ], similar to those for sheep [ 24 , 41 , 59 ] and lower than those for goat and cow milk [ 24 , 41 , 57 ] ( Table 2 ). A slight increase in the EC during lactation has also been observed in goat and cow lactations [ 57 , 58 ].…”
Section: Resultsmentioning
confidence: 43%
See 3 more Smart Citations
“…By contrast, milk electrical conductivity (EC) significantly increased, starting from the tenth week during lactation, from 2.31 to 3.56 mS/cm ( Table 4 ). These values were higher than those described for buffalo [ 18 ], similar to those for sheep [ 24 , 41 , 59 ] and lower than those for goat and cow milk [ 24 , 41 , 57 ] ( Table 2 ). A slight increase in the EC during lactation has also been observed in goat and cow lactations [ 57 , 58 ].…”
Section: Resultsmentioning
confidence: 43%
“…Regarding the somatic cell count, the data revealed that animals had good sanitary conditions during the study period ( Table 3 ). Studies about SCC in red deer milk are scarce and limited to a few individuals [ 24 , 33 ]. During the interval being studied, an increase in SCC at the end was not observed, unlike the slight increase noticed for a similar period by Pérez Serrano [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, hinds are milked to obtain the milk that is used for cheese production and for other innovative applications in the cosmetic industry. In fact, recent studies have assessed technological variables of red deer milk concluding a good aptitude of this milk for the production of dairy products [39]. Therefore, it is necessary to determine the SCC associated with mastitis in deer.…”
Section: Discussionmentioning
confidence: 99%